1981
DOI: 10.2307/2402493
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Status of Reedswamp in the Norfolk Broads

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. British Ecological Society is collaborating with JSTOR to digitize, preserve and extend access to Journal of Applied Ecology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0
2

Year Published

1983
1983
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 14 publications
0
38
0
2
Order By: Relevance
“…However, it must also be borne in mind that abo\e ground, acute or persistent damage to emergent or emerging buds and culms by mowing (Dinka et al, 1995), grazing (Boorman & Fuller, 1981), or co\'ering by rotting algal mats (Klotzli, 1971) might be sufficient to cause or initiate die-back. Klotzli suggested that alga!…”
Section: F I X a L D I S C L' S S I O Xmentioning
confidence: 99%
“…However, it must also be borne in mind that abo\e ground, acute or persistent damage to emergent or emerging buds and culms by mowing (Dinka et al, 1995), grazing (Boorman & Fuller, 1981), or co\'ering by rotting algal mats (Klotzli, 1971) might be sufficient to cause or initiate die-back. Klotzli suggested that alga!…”
Section: F I X a L D I S C L' S S I O Xmentioning
confidence: 99%
“…Amann-Moser (1975); 3, Barby (1967); 4, Barthelmes (1959); 5, Begemann et al (1982);6, Binz (1980);7, Bird (1961);8, Blab (1984); 9, Blume et al (1976);10, Bonham (1983); 11, Boorman and Fuller (1981);12, Brockmann-Jerosch (1934);13, Bruschin (1975a);14, Bruschin (1975b);15, Bruschin (1975c) 16, Bruschin andKlötzli (1977);17, Burgermeister (1978); 18, Burgermeister and Lachavanne (1980);19, Burnand (1980);20, Buttler et al (1985); 21, Calder and Ducker (1979);22, Dahms (1974);23, Dienst (1986);24, Dienst (1987);25, Dinka (1986);26, Fehlmann (1915);27, Gamma (1935);28, George (1977); 29, Grosch (1978);30, Grosch (1980a);…”
Section: Significance Of Lake·shore Reedbeltsmentioning
confidence: 99%
“…Long-term grazing of areas may change vegetation composition and thereby methane cycling microbial processes. Different species of aquatic herbivores have been documented to consume emergent macrophytes, including waterfowl (feral geese, Mute Swan, and Common Coot), mammals (muskrat, coypu), and fish (grass carp) (Boorman and Fuller 1981, Ostendorp 1989, Lodge 1991, Connors et al 2000. The quantitative effects of these herbivores on methane emission depend strongly on whether grazing occurs below or above the water surface, as discussed earlier for reeds.…”
mentioning
confidence: 96%